(untitled) (Economic and Political Thought, 2015)
Transformations of the Arctic region cause serious implications for both the Arctic countries and other participants of international relations. For the sake of geographical, economic and political conditions, China is one of the countries which pay special attention to monitoring the developments beyond the Arctic Circle. This article examines aspects of Chinese interest in the region in terms of access to raw materials, the future opening of Arctic shipping routes and opportunities to realise research, while rising the problem of the relations with the Arctic countries.